Oral health curriculum to reduce dental caries increment in schoolchildren - Dr Hindol Das; Dr Chandrashekar Janakiram; Dr Venkitachalam Ramanarayanan; Dr Vineetha Karuveettil; Dr Vijay Kumar; Dr Parvathy Balachandran; Dr Balagopal Varma; Prof Denny John (Elsevier, 2023)
Aim or Purpose: To assess the effectiveness of an oral health curriculum intervention in reducing dental caries increment and improving oral hygiene behaviour among high school children in grades 8 to 10 of the Ernakulam district in Kerala, India. Materials and Methods: A cluster-randomized trial with a parallel-group comparative design will be conducted in 2000 high school children. Two arms with a 1:1 distribution will receive either an oral health curriculum intervention from a dental professional or a schoolteacher. DMFT, OHI-S, and KAB will be measured at baseline, after one year (mid-term), and two years (final), respectively, using clinical oral examination and questionnaires. Ethical approval with prospective trial registration and ICMR funding was obtained. Results: In 2 years, expected outcomes-• New dental caries increments not more than 10% due to improved knowledge in dental caries management.• Good oral hygiene index scores due to increased knowledge of oral hygiene habits.• Improvement in knowledge, attitudes, and behaviours regarding oral hygiene post-intervention. Conclusions: If the oral health curriculum intervention is found to be effective in changing children's behaviour positively, it may eventually be incorporated into the school health curriculum, thus improving children's oral health, academic performance, and quality of life. The implementation of a classroom-based intervention could serve as a cost-effective tool to increase children's oral health awareness, leading to better long-term oral health outcomes. This study contributes to the global initiative of making every school a health-promoting school, bringing health and education together to benefit the future generations.